Dielectric behavior and AC electrical conductivity analysis of PMMA films - Hasan, Bushra A. (Iraqi Journal of Physics, 2019)
PMMA films of different thickness (0.006, 0.0105, 0.0206, 0.0385 and 0.056cm) were synthesized by casting process. The temperature and frequency dependence of dielectric constant and AC electrical conductivity measurements at various frequencies (10kHz-10MHz) and temperatures (293-373K) were carried out. Few anomalies in dielectric studies were observed near 313 and 373 K respectively. These points were related to glass transitions temperature. The variation of activation energy and conduction behavior was studied .From the AC conduction studies, it is confirmed that the mechanism responsible for the conduction process is hopping of carriers. The variations of the dielectric constant and loss as function of frequency at different temperature was observed and the results were discussed. The calculated activation energy varied with the thickness, temperature, and applied frequency. Conductivity plots against frequency suggested that the response obeying the universal power law concerning the AC conductivity and dielectric behavior of polymer. The polarizability a increases with temperature but decreases with thickness indicating weekends and rising of intermolecular forces respectively.